Increasing Motivation to Study Physics Using PhET Media on Mechanical Energy Material - Haris Munandar; Aris Doyan; Susilawati Susilawati; Syamsul Hakim; Lalu Muliyadi; Hamidi Hamidi (MANDALIKA : Journal of Social Science, 2024)
This activity is a collaboration carried out with SMAN 5 Mataram. This study aims to assist teachers in increasing student motivation in the physics learning process. This study was carried out through three stages, namely preparation, implementation, and reflection. The result of this activity is to create a fun learning process for students, so that students are increasingly motivated to learn to actively explore and build their knowledge. Learning that is carried out is more student-centered